Diagnostic value of NT-proCNP compared to NSE and S100B in cerebrospinal fluid and plasma of patients with sepsis-associated encephalopathy. (23rd January 2019) - Ehler, Johannes; Saller, Thomas; Wittstock, Matthias; Rommer, Paulus S.; Chappell, Daniel; Zwissler, Bernhard; Grossmann, Annette; Richter, Georg; Reuter, Daniel A.; Nöldge-Schomburg, Gabriele; Sauer, Martin
Highlights: Plasma NT-proCNP levels are highly elevated in sepsis patients with SAE. Plasma NT-proCNP levels might be of clinical value for the detection of SAE. CSF and plasma NT-proCNP levels correlate in patients with SAE. This correlation suggests a link between systemic and neuroinflammation in SAE. Plasma NT-proCNP measurement might be superior to S100B and NSE in SAE. Abstract: Sepsis-associated encephalopathy (SAE) has significant impact on the neurocognitive outcome of sepsis survivors. This study was conducted to analyze the amino-terminal propeptide of the C-type natriuretic peptide (NT-proCNP) as a biomarker for SAE in comparison to neuron-specific enolase (NSE) and S100B protein. Cerebrospinal fluid (CSF) and plasma samples from twelve septic patients with SAE and nine non-septic controls without encephalopathy were analyzed. The assessment of SAE comprised a neuropsychiatric examination, delirium screening using the confusion assessment method in the ICU (CAM-ICU) and magnetic resonance imaging (MRI) in all participants. NSE, S100B and NT-proCNP were measured in plasma at study days 1, 3 and 7 in sepsis patients, once in controls and once in the CSF of both groups. The long-term outcome was assessed using the validated Barthel index (BI). Plasma NT-proCNP levels were significantly higher in the sepsis cohort compared to controls with peak concentrations at study day 1 (10.1 ± 6.6 pmol/l vs. 3.3 ± 0.9 pmol/l; p < 0.01) and a decrease over time. Plasma NT-proCNP levels at day 7 correlated with NT-proCNP in CSF (r = 0.700, p < 0.05). A comparable decrease of significantly higher plasma S100B values in sepsis patients compared to controls was observed. Plasma NSE levels were not significantly different between both groups. CSF NT-proCNP levels just tended to be higher in sepsis patients compared to controls and tended to be higher in patients with septic brain lesions seen on MRI. In the sepsis cohort CSF NT-proCNP levels correlated with CSF Interleukin-6 (IL-6) levels (r = 0.616, p < 0.05) and systemic inflammation represented by high plasma procalcitonin (PCT) levels at day 3 (r = 0.727, p < 0.05). The high peak concentration of plasma NT-proCNP in the early phase of sepsis might help to predict the emergence of SAE during the further course of disease. NT-proCNP in plasma might, in contrast to CSF, indicate neurological impairment in patients with SAE.